Destroying an American Dream: How Does Financial Uncertainty Change Representations about Life in the USA - Zhidkova, Polina (Journal of Economic Sociology, 2018)
This book by Jonathan Morduch and Rachel Schneider allows us to be immersed in the life of American families and to discover the most hidden area of family life— financial well-being. Reading this book, it is possible to find out how household income is formed, how money is spent, how savings are made, what kind of debt practices are applied and, most importantly, what problems and decision-making processes Americans have to face on this difficult path. The authors compare the financial path of the study participants to a rocky road, and their lives to a struggle in a world of uncertainty. The researchers show that the main problem for people in the US is not low income but instability, which leads to the fact that families live far from the normal financial patterns for almost half the year. The results show how far American families are from the predictions of Franco Modigliani’s lifecycle model and how misunderstood they remain by the main programs of social support which are mainly built around long-term plans and specific goals such as retirement savings, while families need short-term assistance—to live to the next month. The research topic is, of course, extremely urgent, and its implementation deserves recognition in the methodological field of research into the financial behavior of families. This is an example of financial ethnography, which is embodied in the book and can bring each reader closer to understanding how real families live on another continent and what problems they have to face.